BUILDING A PROSPEROUS AND HEALTHY FAMILY THE ROLE OF CLEAN AND HEALTHY LIVING BEHAVIORS IN DISEASE PREVENTION - Purwanti, Yanik; Dhuha, Ahmad Naajih Syamsi; Fauriah, Nikmatul (Journal of Social Comunity Services, 2024)
General Background: Family health is a foundational element for building a prosperous society, and Clean and Healthy Living Behavior (PHBS) plays a crucial role in disease prevention and quality of life improvement. Specific Background: PHBS encompasses various aspects, including sanitation, hygiene, and stress management, which are vital for ensuring family well-being. However, the adoption of PHBS remains uneven across communities, presenting barriers to achieving widespread health benefits. Knowledge Gap: While the importance of PHBS is recognized, there is a lack of effective strategies to raise public awareness and encourage long-term implementation, particularly at the family level. Aims: This study aimed to assess the impact of health information literacy workshops on community awareness and adoption of PHBS, focusing on disease prevention and lifestyle changes within families. Results: The workshop successfully increased public knowledge about PHBS, motivating participants to adopt healthier practices in their daily lives. It also raised awareness about the connection between family health and community well-being, with participants reporting greater intention to implement PHBS in their households. Novelty: This study highlights the effectiveness of workshop-based interventions as a tool for improving health literacy and promoting the widespread adoption of PHBS, especially within family units. Implications: The findings suggest that targeted educational programs, combined with community-based initiatives, can significantly contribute to disease prevention and improve public health outcomes, emphasizing the role of families as key actors in fostering healthier societies.